Foreign Direct Investment Strategies in Shandong Province - Lin, Lyu; San Gabriel, Hilda (Journal of Theory and Practice in Economics and Management, 2025)
The investment of foreign investors has been rampant in China because of rapid growth and mobilization of global economies. The increasing competition in the international market led business enterprises need to create and implement strategies for attracting foreign direct investment. Using international investment theories, this research aims to analyze and provide a theoretical basis for the creation of practical strategies in engaging foreign direct investments in Zibo City and Qingdao City. A qualitative analysis, this research determined how economic and political stability, business environment, market size and growth potential as well as investment incentives and regulations affect foreign direct investments in both cities. Focus group discussions were among the main methodologies that ushered the identification of effective strategies which the respondents’ business enterprises could use in implementing their own operational management in order to pave the way for foreign direct investment. In essence, this research hopes to contribute practical and theoretical significance that would aid the economic stability in Shandong Province through its business enterprises.